Analysis of Parking Characteristics and Demand in Teratai Traditional Market, Pontianak - Amanda, Sherin; Azwansyah, Heri; Kadarini, S. Nurlaily (Fakultas Teknik Universitas Tanjungpura, 2024)
The Teratai Traditional Market in Pontianak, Indonesia, faces significant transportation challenges, particularly regarding parking management amid increasing vehicle ownership. The analysis focused on the parking patterns, utilization rates, and efficiency across various zones within the market. The study revealed that Zone A experiences the highest motorcycle activity, especially on weekends, with a utilization rate of 66%. In contrast, car parking in this zone remains limited, with a high turnover but insufficient spaces, resulting in an overcapacity index of 150%. Zones B to E display varied motorcycle and car usage, with motorcycle parking consistently outstripping car usage. The parking area is often inefficient due to irregular vehicle arrangements, lack of surface maintenance, and interference from street vendors, leading to congestion. Improvements include introducing designated markings, restructuring parking angles, and enhancing surface conditions to optimize space and reduce bottlenecks. The analysis recommended expanding motorcycle spaces and better-managing car parking to meet demand. Realignment plans propose 255 motorcycle slots and 12 car spaces, suggesting sufficient motorcycle capacity but a continued shortage of cars. These measures aim to enhance market accessibility, streamline traffic flow, and provide a more efficient parking system for visitors and vendors alike.